Performance characteristics of packed bed thermal energy storage for solar thermal power plants - Allen, Kenneth Guy (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2010.